Risk management in construction industry - Fatin Izzati, Sulaiman (2017)
Managing risk during construction period is very important process in order to achieve the project objective in terms of safety and health, cost, time and quality. Four elements in managing the risk effectively are begun by establishing organizational structure, process and resources to enhance its performance. Therefore, this study is carried out to identify the risk that always occur in construction industry and also to determine the factor of risk in order to carried out the solution to prevent risk from occur. The study involved the G7 contractors registered with CIDB that have been involved in project area of Kuala Lumpur and also Kuantan. The total of 130 questionnaires was distributed and only 109 were returned answered which give a value of 84%. From the study, the risks that always occur in construction are machine and equipment problem and also manpower resources problem. Factor that contributes to the risk in construction industry are lack of site safety inspection and supervision, lack of adequate tool and equipment, lack of safety knowledge, lack of adequate lighting and also lack of compliance to governmental safety regulation. In order to minimize the risk and also to prevent the risk from occur, well planning of project process before project start should be done firstly follow by well manage machinery and equipment, established an efficient communication at the work place, assign a risk engineer and also develop the risk management workshop for employees.